Biometric radiographic features between foot lesions and long toe under-run heel in donkeys - El-Marakby, AI; Abdelgalil, AI; Mostafa, MB; Soliman, AS (Journal of the Hellenic Veterinary Medical Society, 2022)
Abstract The present study aimed to document the relationship between biometric foot measurements and different radiographic lesions in a group of donkeys’ feet with long toe under-run heel. The common radiographic foot lesions were pedal osteitis complex in 26 (86.6%) and navicular bone reaction in 8 (26.7%). Osteophyte reaction was identified at proximal phalanx in 8 (26.7%) and middle phalanx in 10 (33.3%). Pastern and coffin joints osteoarthritis were found in 4 (13.3%) and 9 (30%) respectively. Palmar soft tissue calcification and eminence of 2nd phalanx were reported in 5 (16.6%) and 1 (3.3%) respectively. The dorsal hoof wall angle (DHWA) was positive significantly correlated with the axis of the distal phalanx, distal phalanx and proximal palmar cortex angles, the heel angle, and distal phalanx solar border angle. The increased dorsal hoof wall length (DHWL) was positive strongly correlated with dorsal coronary band height, medial wall length, lateral wall length, lateral coronary band distance, medial coronary band distance, lateral distal phalanx to bottom distance, and medial distal phalanx to bottom distance. The dorsal hoof wall and heel angles reflected increased stress on the hoof capsule, distal interphalangeal joint, navicular bone, and palmar soft tissue structures. The low heel, the distal phalanx solar border angle and under development of the palmar section of the hoof indicated distal phalanx was slightly slippage dorsally, increased tension on the DDFT, navicular bone, and pedal osteitis complex in long toe under-run heels. This study demonstrated a relationship between biometric foot measurements and the presence of radiographic foot lesions detected in long toe under-run heel in donkeys.